The Role of Systemic Steroid Administration in Meniere's Syndrome: A Case Report - Krizdiana, Usqi (Sriwijaya Journal of Otorhinolaryngology, 2023)
Introduction: Meniere's syndrome is an inner ear disease characterized by episodes of spontaneous vertigo, tinnitus, hearing fluctuations, and a feeling of fullness in the ear. Treatment varies depending on severity, and systemic steroids may be an option in cases resistant to first-line therapy. This case report aims to present treatment for Meniere's syndrome. Case presentation: We report the case of a 35-year-old woman with Meniere's syndrome who did not improve with standard therapy. The patient was given oral prednisone 40 mg per day for 5 days, followed by tapering the dose for 2 weeks. Conclusion: Administration of systemic steroids to these patients resulted in significant improvement in symptoms of vertigo, tinnitus, and hearing fluctuations. The patient did not experience any significant side effects.